PERAN ETIKA PROFESI DAN HUKUM PERBURUHAN DALAM MEMBANGUN MOTIVASI DAN PRIBADI UNGGUL MAHASISWA - Irianto (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
This study aims to reveal the role of professional ethics and labour law in shaping the motivation and personal excellence of mechanical engineering students at Bontang College of Industrial Technology (STTI). Professional ethics and labour law play an important role in guiding students to develop high motivation and personal excellence during their studies. This research uses qualitative methods with in-depth interviews and document analysis as data collection techniques. The research respondents were active students of Mechanical Engineering at STTI Bontang. The results showed that understanding professional ethics provides a moral foundation for students to develop a positive professional attitude. Meanwhile, knowledge of labour law provides a better understanding of the rights and responsibilities related to employment. These two factors have a positive impact on students' motivation to achieve academic excellence and personal development. In addition, professional ethics and understanding of labour law also contribute to the formation of students' personal character, including integrity, responsibility and awareness of rights and justice. Students who understand the values of professional ethics and labour law tend to have higher intrinsic motivation and develop personal excellence. This research provides a better understanding of the important role of professional ethics and labour law in guiding students' personal character.